2002
DOI: 10.1080/09613210110102238
|View full text |Cite
|
Sign up to set email alerts
|

The building stock as a research object

Abstract: Activities related to refurbishment of the building stock as a percentage of all building work have been constantly growing in most central European countries over the last 20 years. The main argument in this paper is the need to improve knowledge about composition of the existing building stock, the dynamics of its transformation and to relate this to the different actors in property professions. A review is presented of traditional and new sectoral research approaches to partial or national building stocks t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
152
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 252 publications
(156 citation statements)
references
References 6 publications
2
152
0
2
Order By: Relevance
“…Existing building stock is an important physical, economic, social and cultural capital to any nation (Kohler and Hassler, 2002). Building obsolescence/redundancy is identified as one of critical issues associated within the existing building stock.…”
Section: Introductionmentioning
confidence: 99%
“…Existing building stock is an important physical, economic, social and cultural capital to any nation (Kohler and Hassler, 2002). Building obsolescence/redundancy is identified as one of critical issues associated within the existing building stock.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing recognition that public policy needs to be evidence based, and for different policy strategies related to the building stock to be tested and evaluated according to that evidence. Kohler and Hassler (2002) considered 'the building stock as a research object' and concluded that as of now:…”
mentioning
confidence: 99%
“…(Kohler and Yang, 2007, p. 4). By relating these different notions of human, social and cultural capital, even if the definitions do not always coincide, an unusual opportunity is created for transdisciplinary research (Kohler and Hassler, 2002;Hassler and Kohler, 2001). The built environment is both a dominating part of the manmade physical capital, and a principle ingredient in the social capital in the sense that it constitutes the place for social relations (Lawrence and Low, 1990, p. 484).…”
Section: Current Perspectives Promising Methods Missing Piecesmentioning
confidence: 99%